The Effect Of Learning Videos on Problem Solving Ability in Chemistry Learning through Google Classroom At SMAS Muhammadiyah Maumere - Aldi Gunawan; Kartini Rahman Nisa; Kristina Tresia Leto; Sunarwin Sunarwin; Apriani Megati (Universitas Lampung, 2022)
The Effect Of Learning Videos On Problem Solving Ability In Chemistry Learning Through Google Classroom At Muhammadiyah Maumere SMAS. The COVID-19 outbreak has caused various negative effects, one of which is in the field of education. Schools in Indonesia implement an online learning system because it is to suppress the spread of the COVID-19 virus. This study aims to determine the effect of learning videos on students' problem solving abilities. The sample in this study were 19 students of class XI MIPA. The sampling technique used is a non-probability sampling technique, especially the saturated sampling technique. This research uses descriptive quantitative method. The results of this study are the results that learning videos have an influence on the problem solving ability of chemistry learning through google classroom at SMAS Muhammadiyah, this is based on the results of the t test.